The Hydraenidae of Cuba (Insecta: Coleoptera) I: Contribution to the fauna of eastern Cuba - Deler-Hernández, Albert; Delgado, Juan A. (Zootaxa, 2012)
Beginning in eastern Cuba, a systematic survey on the aquatic beetle fauna of that country is presently being carried out.We present a comprehensive account of the six species of the family Hydraenidae (Insecta: Coleoptera) so far collectedin this region. A new species, Hydraena franklyni is described. Detailed data on the new record of H. guadelupensis andthe four previously known Cuban species are also included. Remarks on their external morphology, descriptions of somemorphological features not previously described, distributional maps, and notes on their ecology are given for all sixspecies. In order to facilitate their identification, a simple key to adults of the six species is provided. Although the faunaof Hydraenidae in eastern Cuba may not include further species, the total Cuban fauna of this family is not yet completely known.